Efficient gene correction of an aberrant splice site in β‐thalassaemia iPSCs by CRISPR/Cas9 and single‐strand oligodeoxynucleotides. Issue 12 (21st October 2019) - Xiong, Zeyu; Xie, Yingjun; Yang, Yi; Xue, Yanting; Wang, Ding; Lin, Shouheng; Chen, Diyu; Lu, Dian; He, Lina; Song, Bing; Yang, Yinghong; Sun, Xiaofang
Abstract: β‐thalassaemia is a prevalent hereditary haematological disease caused by mutations in the human haemoglobin β (HBB) gene. Among them, the HBB IVS2‐654 (C > T) mutation, which is in the intron, creates an aberrant splicing site. Bone marrow transplantation for curing β‐thalassaemia is limited due to the lack of matched donors. The clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR‐associated protein 9 (Cas9), as a widely used tool for gene editing, is able to target specific sequence and create double‐strand break (DSB), which can be combined with the single‐stranded oligodeoxynucleotide (ssODN) to correct mutations. In this study, according to two different strategies, the HBB IVS2‐654 mutation was seamlessly corrected in iPSCs by CRISPR/Cas9 system and ssODN. To reduce the occurrence of secondary cleavage, a more efficient strategy was adopted. The corrected iPSCs kept pluripotency and genome stability. Moreover, they could differentiate normally. Through CRISPR/Cas9 system and ssODN, our study provides improved strategies for gene correction of β‐Thalassaemia, and the expression of the HBB gene can be restored, which can be used for gene therapy in the future.